The logical framework methodology in the construction of reversion projects: Case study: Cannabis sativa as a source of food and jobs in Villa del Rosario, Colombia - Arencibia Pardo, Francisco Raúl; Peña Rodríguez, Belisario; Ávila Treviño, Jazmin Anai (Sello Editorial Unipamplona, 2025)
In this research work, the authors identified cannabis sativa as the source of investment projects aimed at small and medium-sized enterprises in the alternative, healthy, and competitive food sector. The work was carried out in Villa del Rosario, department of Norte de Santander, Colombia. To achieve the proposed objectives, the research identified the unmet regional need for work, proposing the Logical Framework Methodology as a tool to plan, execute, and evaluate cannabis sativa as a source of food and employment. The problem, its causes and effects, the stakeholders and their influence, the objectives, their means and ends to achieve it, the logical framework matrix, the associated risks, and the financial feasibility study of the project were all worked on. A preliminary business design was proposed, and a simulation of the process was developed.